ModEx: a general purpose computer model exploration system - Younesy, Hamid; Pober, Joseph; Möller, Torsten; Karimi, Mohammad M. (Frontiers in Bioinformatics, 2023)
We present a general purpose visual analysis system that can be used for exploring parameters of a variety of computer models. Our proposed system offers key components of a visual parameter analysis framework including parameter sampling, deriving output summaries, and an exploration interface. It also provides an API for rapid development of parameter space exploration solutions as well as the flexibility to support custom workflows for different application domains. We evaluate the effectiveness of our system by demonstrating it in three domains: data mining, machine learning and specific application in bioinformatics.